Effect of cobalt chloride and vitamin B^g on the growth and gonadal maturation of goldfish Carassius auratus - Ahilan, B; Jeyaseelan, M J Prince (Indian Journal of Fisheries, 2011)
The investigation was aimed at determining the effect of vitamin B,^ and cobaltchloride on the growth and maturation of goldfish. The fishes were stocked inrectangular cement tanks and fed with artificial feed incorporated with vitaminBj2 and cobalt chloride at three different concentrations. Cobalt chloride incorporatedat 7.5 ppm gave positive results both for gonadal development and growth.Among the doses tested for vitamin Bj^, the 25 ppm concentration had shownhighest response for both maturation and growth.